THE INFLUENCE OF THE QUALITY OF HEALTH CLINIC SERVICES ON THE SATISFACTION OF BPJS USER INMATES IN CLASS IIA PURWOKERTO PRISON INSTITUTIONS - Nisa, Nabilla Khoerun; Warih, Wido Cepaka (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study aims to determine the effect of the quality of health clinic service on the satisfaction of BPJS user inmates at the Class IIA Purwokerto Correctional Institution. The quality of health services is assessed based on eight main dimensions, namely technical competence, access to services, effectiveness, human relations, efficiency, continuity, security, and safety. The sample of this study consisted of 127 prisoners using BPJS who were selected by purposive sampling. The research method used is a quantitative approach with data collection through questionnaires. Data were analyzed using simple linear regression techniques to test the influence between variables of health service quality and inmate satisfaction. The results showed a positive and significant influence between the quality of health clinic services and the satisfaction of BPJS user inmates. Therefore, it is recommended that the Correctional Institution continues to improve health services, especially regarding the convenience of facilities and the competence of medical personnel. Keywords: Service Quality; Prisoner Satisfaction; BPJS